C# for Java programmers - Bagnall, Brian, 1972- (Rockland, MA. : Syngress Pub., 2002)
Java Programmers, Preprare for Microsoft's .NET initiative while enhancing your repertoire and marketability with C# for Java Progammers! C#for Java Programmers will prepare readers for the .NET framework by building on what they already know about object-oriented languages and give them the means to maintain their flexibility and effectiveness in an un-certain marketplace. This book will compare and contrast the advantages and disadvantages of both Java and C# to allow programmers to make their own decisions regarding what each language is best used for. Whatever your feelings are about Microsoft and its .NET initiative, there can be no denying that C#is here to stay. The C# language, a close cousin to Java, is a new object-oriented programming language (OOPL) designed to work within the .NET framework. It improves upon many of the vague or ill-defined areas of C++ that frequently lead programmers into trouble. C# is a strongly-typed, object-oriented language designed to give the optimum blend of simplicity, expressiveness, and performance. Written specifically for Java programmers. C# for Java Programmers is not an introductory guide to C#, but builds on what Java programmers already know about object-oriented languages to give them an efficient means for making in-roads to the .NET framework. Compare and Contrast. This book will compare and contrast many of the advantages and drawbacks of Java and C# to allow programmers to make informed, intelligent decisions based on the unique uses of each language. Make your own in-depth analysis of C#and Java with the Syngress Wallet CD. Accompanying each book will be a wallet CD containing the HTML version of the text and in-depth code comparison to allow programmers to see for themselves the various differences between Java and C#.
Part 1: Language Similarities -- 1. An Introduction to C# -- 2. Language Fundamentals -- 3. Declarations and Access Controls -- 4. Operators and Assignments -- 5. Flow Control -- 6. Exception Handling -- 7. Garbage Collection -- Part 2: Language Features not in Java -- 8. Enumerators -- 9. Structs and Properties -- 10. Pointers, Delegates and Primitive Parameters by Reference -- 11. Boxing and Unboxing -- 12. Working with native DLL's -- 13. Interoperation with COM -- Part 3: .NET's Basic Class Libraries vs. Java's Class Libraries -- 14. Strings -- 15. Input/Output -- 16.Networking -- 17. Threading -- 18. Collections -- 19. Reflection -- CD-ROM Contents: -- C# keywords and their Java equivalent -- Example codes for the key differences between the two languages -- A copy of the .Net's Basic Class Library API's.
"Download all of the source code from www.syngress.com"--Cover.
Includes index.
Keywords: C# (Computer program language).; Java (Computer program language).; Electronic books